EKSTRAKSI MINYAK DENGAN METODE WET RENDERING DARI BUAH PANDAN (Pandanus conoideus L) - Murtiningrum, Semangat Ketaren, Suprihatin dan Kaseno (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTPandanus fruit is an alternative source for food oil. The extraction using wet rendering method by which the fresh fruit is boiled in stainless steel container resulted 15,92 percent of net product (dry weight) with the best physical and chemical characteristics i.e. melting point 22,7 oC, viscosity 46,12 cp, color (L value) 29,14, free fatty acids 20,47 percent, peroxide value 4,36 mgO2/100 g, saponification value 206,83, iodine value 63,12, phosphor 87,87 ppm, iron 36,62 ppm, calcium 159,92 ppm and -carotene content 123,0 ppm. Pandanus oil mostly contains mono unsaturated fatty acids which is dominated by oleic acid 52,50 percen,t and saturated fatty acids by palmitic acid 16,04 percent.Key words : pandanus, oil, rendering